2020
DOI: 10.1016/j.clinbiomech.2020.105052
|View full text |Cite
|
Sign up to set email alerts
|

The performance of resurfacing implants for focal cartilage defects depends on the degenerative condition of the opposing cartilage

Abstract: Background: Non-degradable resurfacing implants are being developed for treatment of focal cartilage defects. Performance of these implants has been investigated opposing intact cartilage. This study investigates whether implants would perform equally well when the opposing cartilage is fibrillated. Methods: Human osteochondral strips (~2x1x1 cm) with a smooth (n = 9) or fibrillated (n = 17) cartilage surface were obtained from human tibial plateaus excised during total knee arthroscopy. A custom-made pin-onpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…8,9,17 This is of particular importance, since contact mechanics of PCU against a rough surface, such as an arthritic joint surface, both exhibit and induce accelerated wear. 18 Navigated resurfacing has already been described with positive outcomes in humans and laboratory animals. [19][20][21][22] Comparisons between several studies showed that surgical guides improved the surgical outcome and decreased surgery time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,17 This is of particular importance, since contact mechanics of PCU against a rough surface, such as an arthritic joint surface, both exhibit and induce accelerated wear. 18 Navigated resurfacing has already been described with positive outcomes in humans and laboratory animals. [19][20][21][22] Comparisons between several studies showed that surgical guides improved the surgical outcome and decreased surgery time.…”
Section: Discussionmentioning
confidence: 99%
“…8 9 17 This is of particular importance, since contact mechanics of PCU against a rough surface, such as an arthritic joint surface, both exhibit and induce accelerated wear. 18…”
Section: Discussionmentioning
confidence: 99%
“…Early intervention osteochondral therapies in the form of metal focal knee resurfacing implants (FKRIs) are currently one of the treatment options used to repair cartilage defects in these patients 3–5 . However, as the biomechanical properties of metal implants do not match those of cartilage, these implants can cause a gradual increase in the amount of cartilage damage in the surrounding and opposing tissue 6–10 . In addition to this, MRI diagnostics can no longer be used to visualize and monitor future or recurrent complaints when metal FKRIs are used.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 , 5 However, as the biomechanical properties of metal implants do not match those of cartilage, these implants can cause a gradual increase in the amount of cartilage damage in the surrounding and opposing tissue. 6 , 7 , 8 , 9 , 10 In addition to this, MRI diagnostics can no longer be used to visualize and monitor future or recurrent complaints when metal FKRIs are used.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, these implants are made of metals. These materials are much stiffer than the native cartilage it replaces and the articulating surfaces of these implants lack lubricating properties, leading to damage of the opposing and adjacent cartilage, [4][5][6][7] especially when the implants protrude above the surrounding articulating cartilage surface or are placed at an angle. [8][9][10][11] As an alternative to rigid metal implants, hydrogels are gaining attention as a matrix material for soft tissue replacement.…”
Section: Introductionmentioning
confidence: 99%